Asymptomatic phaeochromocytoma in a patient with Holt-Oram syndrome: a case report. Issue 4 (9th November 2019) - Ng, Perryn; Deepak, Doddabele; Teo, Lynette; Low, Ting Ting
Abstract: Background: Holt-Oram syndrome (HOS) is a rare congenital disease that affects the heart and upper limbs. Phaeochromocytoma, a catecholamine-secreting tumour, is a rare neuroendocrine disorder. We present an interesting case presentation of these two rare disorders in a patient who was asymptomatic for phaeochromocytoma. Case summary: A 28-year-old woman who was diagnosed at birth with HOS, presented to the hospital with heart failure. She has a past medical history of corrected cyanotic congenital heart disease. She presented with dyspnoea but she did not have headaches, tremors, or diaphoresis. Cardiac magnetic resonance scan was done to investigate the cause of her heart failure and revealed right ventricular systolic dysfunction and a suspicious adrenal lesion. Magnetic resonance imaging adrenal confirmed the presence of the adrenal lesion and concerns were raised for a possible phaeochromocytoma. Biochemical tests showed raised plasma free metanephrine levels. Gallium-68 DOTA positron emission tomography scan showed intense right adrenal gland uptake in keeping with diagnosis of phaeochromocytoma. Discussion: Phaeochromocytoma appears to be more prevalent in patients who are in a chronic hypoxic state. This hypoxic state has been postulated to cause the proliferation of adrenal tissue and therefore the formation of phaeochromocytomas. The hypoxia-inducing factor, which is increased in patients with phaeochromocytoma, has been identified as one of the key factors driving this process as it modulates genes that regulate angiogenesis and proliferation. Congenital heart defects seen in HOS can progress to cyanotic heart disease if left uncorrected and may have been the driver for the development of phaeochromocytoma in our patient.